THE USE OF PRO-GEAR INNOVATION IN IMPROVING THE UNDERSTANDING OF PROBABILITY TOPICS OF STATISTICS COURSES IN THE DEPARTMENT OF COMMERCE, PORT DICKSON POLYTECHNIC - Noryanti Binti Samsudin; Nur Saádah Binti Mohd Hisam; Noor Suriani Binti Nazruddin (Journal of Management Small and Medium Enterprises (SMEs), 2023)
The purpose of this study is to identify students' interest in and understanding of the probability topic in the Statistics courses after engaging in a demonstration learning session using the Pro-Gear innovation. The research methodology used is a descriptive and experimental method. A total of 42 first-semester Diploma in Marketing students were separated into two equal groups, A and B. Group A experienced demonstration learning that utilized Pro-Gear innovation, while Group B experienced conventional learning that lacked Pro-Gear innovation. The average score from the End of Chapter (EOC) evaluation of both groups was used to assess student understanding. The level of interest of students is analyzed using the survey form distributed to Group A, which went through demonstration learning using Pro-Gear innovation. Based on the average EOC score analysis, group A had a higher average score than group B. The average difference in EOC score is 7.7%. This shows that the level of understanding of a group of students who utilize Pro-Gear innovation is more advanced than that of a group that does not use Pro-Gear innovation. Meanwhile, the survey form analysis reveals a high average mean value for the eight items investigated. Thus, demonstration learning using the Pro-Gear innovation can enhance the understanding and interest of students in the probability topic. Keywords: Demonstration; Innovation; Probability